PERBANDINGAN EFEK PEMBERIAN MADU DAN N-ACETYLCYSTEINE TERHADAP GAMBARAN HISTOPATOLOGIS GINJAL MENCIT (Mus musculus) YANG DIBERIKAN PAPARAN ASAP ROKOK - Debby Sanders; Maria Nindatu; Marissa Matinahoru (PAMERI, 2019)
Honey is a natural ingredient that contains antioxidants. In addition there are also synthetic antioxidants such as N-Acetylcysteine ​​which can neutralize free radicals and prevent kidney damage.This study aims to compare the effects of honey and N-Acetylcysteine ​​on histopathological features of kidney mice given exposure to cigarette smoke.This study uses true experimental with post test only control group design approach. Samples were grouped randomly into control groups and intervention groups. The intervention group was given honey and N-Acetylcysteine ​​then given exposure to cigarette smoke, then observed the difference using the Kruskal-Wallis test and continued with the Mann-Whitney test. The sample of this study uses mice (Mus musculus) male with a body weight of ± 20-30 gr. The results showed no significant difference, with p> 0.05 (P = 0.749) between Honey and N-Acetylsysteine ​​against renal glomerular atrophy of mice given exposure to cigarette smoke. Furthermore, there was a significant difference with p <0.05 (P = 0.029) between honey and N-Acetylsysteine ​​against renal tubular necrosis of mice given exposure to cigarette smoke.